(untitled) (ADINDAMAS: Jurnal Pengabdian Kepada Masyarakat, 2026)
Micro, Small, and Medium Enterprises (MSMEs) are the backbone of the village economy with great potential, but are often constrained in terms of marketing and product introduction to wider markets. This Community Service Program (PKM) was conducted in Bontoa Village, Minasa Tene District, Pangkep Regency, South Sulawesi, with the aim of improving the capacity of MSME actors in utilizing social media as a means of branding and marketing products based on local potential. The implementation method used a participatory training approach (Participatory Rural Appraisal) carried out in three stages: pre-implementation, implementation, and post-implementation (monitoring and evaluation). Evaluation was conducted using a Likert scale 1–5 questionnaire with 10 items covering four dimensions: branding concept knowledge, digital skills, marketing motivation, and follow-up plans. The evaluation results showed an average increase from 37% (pre-test) to 84% (post-test), with a Normalized Gain (N-Gain) Score of 0.75 (high category). The highest gains occurred in branding concept knowledge (N-Gain 0.77) and digital marketing motivation (N-Gain 0.82). This activity proved effective in improving digital literacy of MSME actors and is expected to drive local economic growth through digitalization of village product marketing.